Implementing a framework for action to assess research impact: Case studies on impact assessment from two global research projects of the International Water Management Institute (IWMI) - Bhatt, Yogesh (2005)
Through its research on land and water management, IWMI strives to have a “positive impact on the activities and perspectives of policy makers, water managers and poor rural communities in developing countries” (IWMI, 2001, 10). However, evaluating the impact of research activities is a much-discussed topic and continues to be a challenge. Furthermore, with the growing importance of the concepts such as ‘participation’, ‘capacity building’ and ‘empowerment’, there is an increasing concern to know how to monitor and assess the effect and impact of such qualitative processes. To address these challenges, IWMI developed a framework for assessing the impact of its research in 2003. The framework addresses both conceptual and practical considerations for measuring and tracking impacts of natural resource management research and serves as a road map for IWMI to better assess its contributions towards improved land and water management in developing countries. This paper discusses IWMI’s Framework for Action to assess research impacts, describes a logical thought process for considering nature and scale of desired impacts and the pathways for impact achievement, and outlines a methodology for practical impact assessment. Building on the impact framework, the paper then examines the process of establishing impact and learning systems in two research projects- “Smallholder Systems Innovation in Integrated Watershed Management in Sub-Saharan Africa (SSI)” which is implemented in South Africa and Tanzania; and “Models for Implementing Multiple-use Water Supply Systems for Enhanced Land and Water Productivity, Rural Livelihoods and Gender Equity (MUS)”, which operates in five international river basins in Central America, Africa and Asia. The paper also provides an overview of a diverse set of generic indicators used by IWMI for in evaluating the impact of natural resource management research at local, basin and national levels. Finally, the paper discusses how impact evaluation can be made con-current process in the life cycle of the projects and established as a powerful learning tool, not only for